MENINGKATKAN KEMAMPUAN MOTORIK KASAR MELALUI PERMAINAN TRADISIONAL â€œSIKODOKAâ€ BAGI ANAK USIA DINI BERLATAR BELAKANG TUNA GRAHITA - Mientje Ratoe Oedjoe; Beatriks Novianti Bunga (Jurnal Ilmiah Visi, 2016)
Physical development in some children with intellectual disability could be delayed. This physical delays can trouble their movement skills. Therefore these children need practices that could improve their gross motoric skills. This research aimed to try out Sikodoka game in order to improve gross motor skills in young children with intellectual disability. Method used was class action research conducted in two cycles and four meetings. Research participants were three young children aged seven to nine years old. The research was conducted in August 2016 taking palce in Kelapa Lima Special Needs School, Kupang. Data collection techniques used were observation and test. Gross motor skills indicators were jumping with one foot skill, jumping with both feet, keeping body balance while collecting â€œeraâ€, tossing â€œeraâ€ correctly inside the square, and grasping â€œeraâ€ skillfully. Results showed that there was improvement in gross motor skills with mean improvement from pre-cycle 38% increased 23% to 61% in cycle 1. From cycle 1 to cycle 2 improved again 43% making the condition after cycle 2 was 95%. According to the evaluation, recommendations to teachers are to be sensitive to childrenâ€™s condition that are easy to be divided in their focus, using reward system to attract childrenâ€™s attention, need to compliment more, uses clapping variations to recover childrenâ€™s focus, reducing activities that could trigger loud activities, using simple languages, dividing sentences that are clear and not long, and reprating games because children with intellectual disability are easy to forget.